Rock engineering - Palmstrom, Arild; Stille, Hakan (ICE Publishing, 2015)
'Rock Engineering' provides a comprehensive explanation of the geological principles and ground investigations involved with geotechnical design and engineering of underground projects. It offers an internationally applicable, practical guide for engineers and geologists responsible for considering different ground conditions, design and planning for excavation and underground projects.